Simultaneous extracorporeal membrane oxygenation and therapeutic plasma exchange procedures are tolerable in both pediatric and adult patients. Issue 4 (10th October 2013) - Dyer, Mitchell; Neal, Matthew D.; Rollins‐Raval, Marian A.; Raval, Jay S.
<x xml:space="preserve">Abstract</x> Background Extracorporeal membrane oxygenation (ECMO) has been used in patients with pulmonary and/or cardiac disease. In rare circumstances, some patients may have to undergo simultaneous therapeutic plasma exchange (TPE). We sought to characterize simultaneous ECMO and TPE procedures at our institution. Study Design and Methods Retrospective analysis of medical records was performed for patients who underwent simultaneous ECMO and TPE. Patient demographics, diagnoses, TPE indications and variables, procedural complications, blood use, laboratory data, and outcomes were collected. Results Seventy‐six patients underwent 293 simultaneous ECMO and TPE procedures; the majority involved pediatric patients, and most patients weighed less than 15 kg. In children, the two most frequent reasons for ECMO were congenital cardiac disease and sepsis; in adults, they were congestive heart failure or cardiomyopathy and severe pulmonary disease. In children, the two most frequent indications for TPE while on ECMO were multisystem organ failure and coagulopathy; in adults, they were humoral rejection of cardiac and pulmonary allografts. Blood product utilization during simultaneous ECMO and TPE was substantial in all patients. The complications of simultaneous ECMO and TPE were hypocalcemia (47 and 27.6% in children and adults, respectively) and hypotension (22.1 and 34.2% in children and adults, respectively). Approximately 45% of children and adults had resolutions of their apheresis indications after completing their TPE regimen. Conclusions Despite the hypocalcemic and hypotensive reactions that occurred during simultaneous ECMO and TPE, apheresis treatment regimens were successfully completed in all patients. With clear communication between ECMO and apheresis teams, along with close patient and instrument monitoring, simultaneous ECMO and TPE is tolerable and can be performed in critically ill children and adults.